THE INFLUENCE OF MOTIVATION, NON-FINANCIAL COMPENSATION, AND WORK DISCIPLINE ON EMPLOYEE JOB SATISFACTION PT BPD KALTIM KALTARA SHARIA BRANCH BALIKPAPAN - Dewi Safitri, Putriani; Hasan, Syahril; Yuliani, Tutik (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
The purpose of this study is to determine the effect of motivation, non-financial compensation, and work discipline on employee job satisfaction at PT BPD Kaltim Kaltara Sharia Branch Balikpapan. The type of research used is quantitative research. The analytical tool used is multiple linear regression. Sampling technique in this research uses census/population sampling technique with total population of 68 employees at PT BPD Kaltim Kaltara Sharia Branch Balikpapan. Data collection method is done by distributing questionnaires, interviews, and observations. Data processing in this research uses SmartPLS program. The result shows that Motivation variable (X1) has partial effect on Job Satisfaction variable (Y) of PT BPD Kaltim Kaltara Sharia Branch Balikpapan employees, Non-Financial Compensation variable (X2) has no partial effect on Job Satisfaction variable (Y) of PT BPD Kaltim Kaltara Sharia Branch Balikpapan employees, and Work Discipline variable (X3) has no partial effect on Job Satisfaction variable (Y) of PT BPD Kaltim Kaltara Sharia Branch Balikpapan employees. Keywords: Work Discipline; Job Satisfaction; Non-Financial Compensation; Motivation